Gene expression of transporter proteins in murine mammary epithelial HC11 cells - Ramezani, Mehrafarin (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2012)
Milk is primary food of infants and indispensable part of human diet. There is solid evidence of chemicals and drugs presence in milk which raise concerns for toxicological safety of milk. Membrane transporters play key role in the transport of chemicals into milk. Transporters belong to ABC transporter superfamily e.g. Bcrp, Mdr1 and Mrp1 or SLC transporter family e.g. Oatp3 and Octn1. Another considered issue is mastitis which is inflammation of mammary gland usually due to bacterial infection. Two major causes of mastitis are Staphylococcus aureus and Escherichia coli. In this project we studied gene expression of several ABC transporters; Bcrp1, Mdr1, Mrp1 and SLC transporters Oatp3 and Octn1 in murine mammary epithelial HC11 cells differentiated into secreting phenotype. We compared two different cell differentiation protocols on HC11 cells and their potential effect on gene expression of membrane transporters. We also investigated effects of S. aureus infection and endotoxin treatment (LPS) on gene expression of transporters. Expression of transporters was studied by SYBR Green RT-PCR.